2015
DOI: 10.1159/000367735
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Markers for Hepatocellular Carcinoma: Simple and Significant Predictors of Outcome in Patients with HCC

Abstract: Background: The effectiveness of tumor markers in evaluating outcomes of patients with hepatocellular carcinoma (HCC) remains to be clarified. Summary: The usefulness of the HCC tumor markers, alpha-fetoprotein (AFP), Lens culinaris agglutinin-reactive fraction of alpha-fetoprotein (AFP-L3), and des-gamma-carboxy prothrombin (DCP) was reviewed. Elevations in these tumor markers at the time of HCC diagnosis correlate with disease progression as assessed by both imaging studies and pathologic examinations. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 66 publications
8
106
1
Order By: Relevance
“…In a previous study, we reported that the duration of administration was a significant prognostic factor for sorafenib treatment. A blood chemical test related to liver functions, such as serum levels of bilirubin as well as the tumor markers alpha-fetoprotein (AFP) and des-gamma carboxyprothrombin (DCP), could also be a marker predicting an overall survival (OS) [31,32,33,34]. In the current study, we retrospectively investigated 356 HCC patients treated with sorafenib at the Kinki University Hospital to elucidate the efficacy of sorafenib treatment and the clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported that the duration of administration was a significant prognostic factor for sorafenib treatment. A blood chemical test related to liver functions, such as serum levels of bilirubin as well as the tumor markers alpha-fetoprotein (AFP) and des-gamma carboxyprothrombin (DCP), could also be a marker predicting an overall survival (OS) [31,32,33,34]. In the current study, we retrospectively investigated 356 HCC patients treated with sorafenib at the Kinki University Hospital to elucidate the efficacy of sorafenib treatment and the clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence levels and recommended grades are listed to assist the diagnosis and treatment of HCC in daily clinical practice. The surveillance and diagnostic algorithm, the most important part of the clinical practice guidelines, recommends regular ultrasound and tumor marker screening using 3 markers (AFP, AFP-L3 and PIVKA-II) [31,32,33] or annual-to-semiannual CT or MRI depending on whether the patients are categorized as very high-risk or high-risk patients. The treatment algorithm presents treatment strategies that are in line with the severity of liver damage and the number and size of tumors [8,9].…”
Section: Clinical Practice Guidelinesmentioning
confidence: 99%
“…In Japan, prothrombin induced by vitamin K absence-II (PIVKA-II), and the L3 fraction of AFP (AFP-L3) [2,3,4] are routinely used alongside AFP to screen for HCC. However, in other countries, the clinical guidelines for HCC, such as those issued by the American Association for the Study of Liver Diseases (AASLD) [5] and the European Association for the Study of the Liver (EASL) [6], do not recommend the use of PIVKA-II or AFP-L3 in daily clinical practice.…”
Section: Tumor Markersmentioning
confidence: 99%
“…AFP-L3 does not correlate with AFP or PIVKA-II in patients with HCC [2,4]. In recent years, the measurement of highly sensitive AFP-L3 has been attracting attention because this innovative method enables AFP-L3 to be measured even when total AFP levels are ≤10 ng/ml.…”
Section: Tumor Markersmentioning
confidence: 99%
See 1 more Smart Citation